John Strype's A survey of the cities of London and Westminster - University of Sheffield - Humanities Research Institute (2007)
"John Stow’s Elizabethan classic, A Survey of London, was first published in 1598, with a second edition following in 1603. Stow (c. 1525-1605) was a chronicler and antiquary who transcribed manscripts and inscriptions rIn the century following Stow’s death, however, the Tudor capital so lovingly depicted and recorded in Stow’s Survey was dramatically transformed. The huge growth of the metropolis, the devastation wrought by the Great Fire of 1666 and the subsequent rebuilding of the City made an updating of the Survey highly desirable. It was to answer this need that John Strype (1643-1737), the ecclesiastical historian and biographer, published a new, hugely expanded version of Stow’s Survey of London in 1720. elating to English history, literature and archaelogy, but his Survey is perhaps his most famous work, with its evocative ‘perambulation’ of the streets of the Tudor capital, which forms the main framework of the book. In 1908, C.L. Kingsford produced a scholarly edition of the 1603 text, which still remains authoritative, although Stow the scholar and antiquary has continued to be investigated by historians since that time." [self-description]